Achievement of complete response to nivolumab in a patient with advanced sarcomatoid hepatocellular carcinoma: A case report - Zhu, Shu-Guang (World J Gastrointest Oncol, 2020)
BACKGROUND: Sarcomatoid hepatocellular carcinoma (SHC) is a rare subtype of hepatocellular carcinoma (HCC), with a high recurrence rate after surgery. In addition to limited effective treatment for the advanced stage of SHC, the prognosis of patients with this malignancy is worse than that of patients with conventional HCC. CASE SUMMARY: We present the case of a 54-year-old man with SHC who underwent radical segmental hepatectomy, which relapsed 4 mo after surgery due to lymphatic metastasis in the porta hepatis. Although a second surgery was performed, new metastasis developed in the mediastinal lymph nodes. Therefore, sorafenib and lenvatinib were sequentially administered as first- and second-line systemic therapies, respectively. However, progressive disease was confirmed based on a recurrent hepatic lesion and new metastatic lesion in the abdominal cavity. Percutaneous transhepatic cholangial drainage was performed to alleviate the biliary obstruction. Because the tumor was strongly positive for programmed death-ligand 1, the patient was started on nivolumab. Imaging studies revealed that after two cycles of immunotherapy, the metastatic lesions decreased to undetectable levels. CONCLUSION: The patient experienced continuous complete remission for 8 mo. Immune checkpoint inhibitors are useful for the treatment of advanced SHC.